The Short Questionnaire to Assess Health-Enhancing Physical Activity in Syrian Adults’ Populations (Epidemiology, Biostatistics, and Public Health, 2024)
Background: To date, no studies have evaluated the reliability and/or validity of methods for measuring physical activity (PA) in free-living conditions within the Syrian population.Methods: This study compared estimates of PA and sedentary behavior (SB) obtained from the ActiGraph WGT3X-TB (AG) accelerometer and the Short Questionnaire to Assess Health Enhancing Physical Activity (SQUASH). Forty-five adults (13 men and 32 women, mean age 36.9 ±8.3 years) completed the SQUASH twice, with a 45-day interval between administrations. Time spent in low, moderate, vigorous, and moderate-vigorous PA (MVPA) was calculated using the SQUASH and AG accelerometer data. Reliability was assessed by calculating the Spearman correlation coefficient between the PA items scores. Bland-Altman analysis was also performed. The validity of the SQUASH was determined using the AG accelerometer as the reference method.Results: PA levels were systematically higher when measured by the SQUASH compared to the AG accelerometer. The Spearman’s correlation coefficient for the overall SQUASH reproducibility was 0.64. The Spearman’s correlation coefficient between the calculated total activity score from the SQUASH and the AG accelerometer was 0.31, indicating moderate reliability and validity of the SQUASH.Conclusion: Given its simplicity, brevity, ease of use, and low cost, the SQUASH appears to be a suitable method for monitoring PA in Syrian adults. Further strengthening of the validity scores may be possible by providing more detailed information on the types of activities included in the questionnaire.
Keywords: Accelerometer; Self-report; Measurements; Reliability; Validity